I WAS AN ACROBAT. AM I IN PAIN?. Issue 4 (1st February 2017) - Martins, Úrsula; Cunha, João; França, Lourenço; Amaro, João; Gomes, Joana; Aguiar Branco, Catarina
Abstract : Background: Acrobatic Gymnastics is a competitive discipline where gymnasts work together, perform acrobatic moves, dance and tumbling. Objective: Investigate the prevalence of musculoskeletal (MS) disorders in former gymnasts. Design: Survey of MS disorders (past and present), sent to former gymnasts. Setting: This study included former gymnasts. Participants: Retired gymnasts of national teams (n=200) and clubs (n=390) from all over the world (16 countries, 4 continents); 612 responders, 590 included according to the inclusion criteria. Interventions: The survey included questions on country, gender, position, years of practice, hours of training/week and competition level, as well as medical information: reason for stopping practice (medical/nonmedical, specify the problem), injuries during practice years, present impact in daily life. Main Outcome Measurements: Proportion (%) who stopped practicing as a consequence of a serious MS injury. Proportion (%) having any current MS disorder. Pre-specified analysis of relationship between training hours/week, competition level, position and % with current MS disorders in the present. Results: Of 590 gymnasts, 294 (50%) reported having suffered a training injury, while 166 (28%) reported still having current medical problems as result of these. A total of 131 gymnasts (22%) reported having stopped practicing because of a medical problem and 121 (21%) reported having a current MS disorder. The most common injury was a traumatic fracture (n=125), most commonly affecting the knee (n=74) and ankle/foot (n=73). As a consequence of the training period, the most common current problems were spine pathology (n=43) and tendinopathies(n=38). Concerning actual symptoms, 402 (68%) reported low back pain, 320 (54%) knee and 219 (37%) shoulder disorders. Conclusions: This is the first study of former gymnasts, allowing us to evaluate the impact of training on the future life quality of the athletes, to identify the most frequent injuries, as well as those with the greatest impact. This may lead to improvements in the treatment of acute injuries, as well as to monitor the level and quality of training, to prevent and also to rehabilitate injuries.